2021
DOI: 10.3389/fmicb.2021.681567
|View full text |Cite
|
Sign up to set email alerts
|

Endophytic Bacterial Isolates From Halophytes Demonstrate Phytopathogen Biocontrol and Plant Growth Promotion Under High Salinity

Abstract: Halophytic endophytes potentially contribute to the host’s adaptation to adverse environments, improving its tolerance against various biotic and abiotic stresses. Here, we identified the culturable endophytic bacteria of three crop wild relative (CWR) halophytes: Cakile maritima, Matthiola tricuspidata, and Crithmum maritimum. In the present study, the potential of these isolates to improve crop adaptations to various stresses was investigated, using both in vitro and in-planta approaches. Endophytic isolates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 59 publications
2
20
0
Order By: Relevance
“…Liu et al, [41] reported that the endophyte community-shaping in apple is being determined by the type of tissue, the sampling site, and cultivar, which in turn have a prominent impact on the number of potential antifungal biota strains present. The plant endosymbiosiomes have been widely used to isolate microflora with biocontrol ability [42] and the studies on such entities have revealed their abilities to contribute in conferring resistance to crops against various phytopathogens, including other substantial benefits on the host such as nutrient acquisition, enhanced growth, and improved resistance to heat, drought, and other stresses [43]. The present study revealed that there is an abundant diversity of bacterial microflora across the Himalayan apple germplasm with respect to their antifungal behavior against V. inaequalis.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al, [41] reported that the endophyte community-shaping in apple is being determined by the type of tissue, the sampling site, and cultivar, which in turn have a prominent impact on the number of potential antifungal biota strains present. The plant endosymbiosiomes have been widely used to isolate microflora with biocontrol ability [42] and the studies on such entities have revealed their abilities to contribute in conferring resistance to crops against various phytopathogens, including other substantial benefits on the host such as nutrient acquisition, enhanced growth, and improved resistance to heat, drought, and other stresses [43]. The present study revealed that there is an abundant diversity of bacterial microflora across the Himalayan apple germplasm with respect to their antifungal behavior against V. inaequalis.…”
Section: Discussionmentioning
confidence: 99%
“…Endophytes, microorganisms that naturally reside in tissues of living plants, are potential sources of novel natural products for exploitation in agriculture, industry, and medicine (Hallmann et al, 1997;El-Tarabily et al, 2009. Bacterial endophytes confer profound impacts on their host plants through promoting growth, increasing tolerance to pathogens, and improving phytoremediation (Ma et al, 2016;Christakis et al, 2021;Faria et al, 2021). In addition, they have the ability to produce a plethora of bioactive secondary metabolites to protect plants against environmental stresses (Khare et al, 2018;Kushwaha et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Direct mechanisms may enhance growth through fixation of nitrogen (N), solubilization of phosphorus (P), sequestration of iron (Fe), and production of plant growth regulators (PGRs), such as auxins, cytokinins (CKs), gibberellins (GA 3 ), ethylene (ET), and abscisic acid (ABA) (Olanrewaju et al, 2017;Gouda et al, 2018). Indirect growth promotion occurs when PGPB reduce the deleterious effects of pathogens on plant growth (Khare et al, 2018;Bektas and Kusek, 2021;Christakis et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The Halophytic environment is also interesting to isolate useful microbes [261]. In an exhaustive study by Christakis et al [85], a total of 115 endophytic isolates were identified from three crop wild relative (CWR) halophytes: Cakile maritima, Matthiola tricuspidata, and Crithmum maritimum. From this selection, many strains showed antagonistic activity against the plant pathogens Verticillium dahliae, Ralstonia solanacearum, and Clavibacter michiganensis and the human pathogen Aspergillus fumigatus.…”
Section: From Microbiome To Pgpms Inoculantsmentioning
confidence: 99%